2005
DOI: 10.1128/aem.71.2.1018-1024.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ethidium Monoazide and PCR in Combination for Quantification of Viable and Dead Cells in Complex Samples

Abstract: The distinction between viable and dead cells is a major issue in many aspects of biological research. We have developed a novel concept for quantification of viable and dead cells in complex samples. The viable/dead stain ethidium monoazide (EMA) is used in combination with realtime PCR to inhibit amplification of DNA from dead cells that have taken up EMA (Fig. 1). Viable/dead determinations are key issues in many aspects of biological research. The current technologies addressing this important issue have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
289
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(295 citation statements)
references
References 30 publications
5
289
0
1
Order By: Relevance
“…Samples were treated as described by Rudi et al (2005a) with slight modifications. Briefly, 1 ml of sample was centrifuged at 13,000×g for 10 min, the supernatant removed and the pellet resuspended in 1 ml of EMA at concentrations of 0, 1, 2, 3, 5, and/or 7.5 μg/ml followed by incubation in the dark at room temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were treated as described by Rudi et al (2005a) with slight modifications. Briefly, 1 ml of sample was centrifuged at 13,000×g for 10 min, the supernatant removed and the pellet resuspended in 1 ml of EMA at concentrations of 0, 1, 2, 3, 5, and/or 7.5 μg/ml followed by incubation in the dark at room temperature for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the advantages of culture‐independent methods, the limitation of molecular assessment (especially for DNA‐based methods) is the possible overestimation of viable cell densities because DNA can persist for an extended period after cell death in environments (Rudi et al ., 2005). Recently, DNA‐intercalating dyes such as ethidium monoazide (EMA) and propidium monoazide (PMA) have been proposed as useful molecular methods to quantify intact bacterial cells in environments (Nogva et al ., 2003; Rudi et al ., 2005; Nocker et al ., 2006). PMA or EMA with PCR technique has been widely used to assess cell viability in water, soil, air and food (Rogers et al ., 2008; Bae and Wuertz, 2009; Miotto et al ., 2012; Kaushik and Balasubramanian, 2013; Li and Chen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Selective nucleic acid intercalating dyes, such as EMA and PMA, represent one of the most successful recent approaches to detect viable cells (as defined by an intact cell membrane) by PCR (Fittipaldi et al 2012) and have been effectively evaluated in different microorganisms Rudi et al 2005;van Frankenhuyzen et al 2011). As both dyes have similar structures, comparable results might be expected; however, some studies have showed differences (Andorrà et al 2010;Cawthorn et al 2008;Chang et al 2010;Nam et al 2011;Nocker and Camper 2009;Pan and Breidt 2007;Wagner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Photolysis of EMA and PMA converts the azide group into a highly reactive nitrene radical, which can react with any organic molecule in its proximity, including DNA. In this bound state, DNA cannot be amplified by PCR (Nocker and Camper 2009;Rudi et al 2005). This promising analytical approach is still in development and needs to be investigated further (Fittipaldi et al 2012).…”
Section: Introductionmentioning
confidence: 99%